Assessing STEM differentiation needs based on spatial ability and engagement: implications for making activities - Flø, Ellen Egeland; Smedsrud, Jørgen Hammer (Frontiers in Psychology, 2025)
IntroductionSpatial ability is robustly correlated with science, technology, engineering, and mathematics (STEM) achievement, but schools have generally not differentiated with regard to this ability. Moreover, the level of involvement, focus, and motivation that students exhibit in school activities, specifically their engagement, also plays a central role in overall achievement. Therefore, this study aims to develop a STEM scale to identify differentiation needs based on spatial ability and engagement. These differentiation needs may be addressed by instructional methods such as making activities, where students design and construct physical objects. Because these activities enhance engagement, can improve spatial ability, and allow students to use their spatial skills, this study also aims to discuss the implications of using making activities for differentiation.MethodsTo address these aims, 535 students from grades 5 to 10 (9–16 years) from two medium-sized suburban and semi-rural municipalities were randomly split into one exploratory and one confirmatory sample, where participants were students. An exploratory and confirmatory item response theory (IRT) approach was used for the data analysis. Correlations of the latent variable were sought for spatial ability and engagement.ResultsThe STEM scale demonstrated good psychometric properties, and the underlying factor of the scale correlated positively with engagement and spatial ability.DiscussionThus, the STEM scale can be useful for educational practice by identifying students needing differentiation concerning their spatial ability level, where their level of engagement is also considered. Making activities could potentially benefit some students more than others, depending on their STEM scale scores.